Internal migration, area effects and health: Does where you move to impact upon your health?. (July 2015) - Green, Mark A.; Subramanian, S.V.; Vickers, Daniel; Dorling, Danny
Abstract: Evidence surrounding the importance of neighbourhood on health has been mostly restricted to observational data analyses. However, observational data are often the only source of information available to test this association and can fail to accurately draw out casual effects. This study employs a pseudo-experimental design to provide a novel test for the evidence of neighbourhood effects on health, using migration as a mechanism for assessing the role of neighbourhood. Coarsened exact matching was employed on the British Household Panel Survey (2006–2008) to analyse the association between migration (by area type, measured using a classification of mortality patterns) and health. Although an overall significant positive association between migration and health was observed, once the effect was disaggregated by location and destination it disappeared. Rather, evidence of health selective migration was found whereby individuals of poorer health migrated to areas that displayed poorer health and social characteristics (and vice versa ). Migration is an important process that through the social sorting of individuals in terms of their health, contributes to the growing polarisation and inequality in health patterns. The study helps to build upon previous research through providing a new and stronger form of analysis that reduces the influence of bias on results. Incorporating this under-utilised methodology and research design in future studies could help develop public health and geographical research. Highlights: Uses a novel pseudo-experimental design to test for neighbourhood effects on health. Migration was statistically associated with poorer health. The effect disappeared once origin and destination were accounted for. We found some evidence of health selective migration.